2019
DOI: 10.1017/s0033291718003999
|View full text |Cite
|
Sign up to set email alerts
|

Levels of early-childhood behavioral inhibition predict distinct neurodevelopmental pathways to pediatric anxiety

Abstract: BackgroundAnxiety symptoms gradually emerge during childhood and adolescence. Individual differences in behavioral inhibition (BI), an early-childhood temperament, may shape developmental paths through which these symptoms arise. Cross-sectional research suggests that level of early-childhood BI moderates associations between later anxiety symptoms and threat-related amygdala–prefrontal cortex (PFC) circuitry function. However, no study has characterized these associations longitudinally. Here, we tested wheth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 83 publications
(170 reference statements)
2
27
1
1
Order By: Relevance
“…Aligning with hypotheses, girls who attended more to a potentially critical judge relative to a positive judge during the AST also showed more positive coupling between the right amygdala and bilateral anterior PFC while receiving social rejection feedback on the Chatroom task. Interestingly, similar prior research has implicated the right amygdala specifically (e.g., Gee et al, 2013 ; Price et al, 2016 ; Abend et al, 2020 ), which could suggest meaningful lateralization. However, lateralized effects could also be related to inadvertent effects from data analysis ( Murphy et al, 2020 ).…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Aligning with hypotheses, girls who attended more to a potentially critical judge relative to a positive judge during the AST also showed more positive coupling between the right amygdala and bilateral anterior PFC while receiving social rejection feedback on the Chatroom task. Interestingly, similar prior research has implicated the right amygdala specifically (e.g., Gee et al, 2013 ; Price et al, 2016 ; Abend et al, 2020 ), which could suggest meaningful lateralization. However, lateralized effects could also be related to inadvertent effects from data analysis ( Murphy et al, 2020 ).…”
Section: Discussionsupporting
confidence: 61%
“…On the other hand, less negative fronto-amygdala connectivity during threat processing may place children and adolescents at risk for anxiety. A substantive literature has linked youth anxiety to altered fronto-amygdala connectivity while viewing negative emotional stimuli (e.g., Monk et al, 2008 ; Strawn et al, 2012 ; Campbell-Sills et al, 2011 ; White et al, 2017 ; Abend et al, 2020 ). Much of this research suggests that youth with anxiety show less negative coupling (or more positive coupling) between the amygdala (particularly the right amygdala) and regions of ventrolateral and medial PFC in response to social threat ( Monk et al, 2008 ; Davis et al, 2019 ) and non-social threat ( Strawn et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, there may be multiple pathways through which a child can develop problems with anxiety, and it could be the case that each pathway/subtype is associated with a different profile of cognitive control dynamics. Previous neuroimaging work has demonstrated that cognitive-control-related neural activity differentiates BI and non-BI anxious youth (Abend et al, 2020; Smith et al, 2019), suggesting that cognitive control could serve as a potential criterion for defining anxious subtypes. However, the present study is the first to characterize how proactive and reactive control each uniquely relate to these pathways/subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence for the association between learning and the development of child psychopathology come from three main areas of research. First, it is well-established that an attentional bias towards aversive facial stimuli (e.g., angry and fear faces) have been linked to the development of anxiety disorders in children (37,(84)(85)(86). Second, children with ASD and conduct problems have difficulties with learning from emotional expressions (87).…”
Section: Learningmentioning
confidence: 99%